Impurity profiling of the strontium ranelate using stability indicating UPLC method and structural elucidation of degradants by LC-MS-TOF with the greenness assessment - Arti Swami, Aarti Shastri, Vishnu Choudhari (Journal of Applied Pharmaceutical Science, 2025)
Strontium ranelate (STR) is an antiosteoporosis agent utilized to form new bone and inhibit bone resorption. STR also activates calcium-sensing receptors, which convert pre-osteoblasts to osteoblasts, promoting bone synthesis, as demonstrated in previous studies. In this study, the objective was to establish a validated, stability-indicating ultra-performance liquid chromatography (UPLC) method for the identification and quantification of impurities in STR under accelerated degradation conditions. The method was optimized employing an ACQUITY photodiode array UPLC C18 BEH (2.1 x 100 mm, 1.7 μm) at room temperature, with a flow rate of 0.2 ml/minutes and sample injection volume of 2 μl. The mobile phase consisted of Ammonium acetate buffer pH 3.0 adjusted with Glacial Acetic acid: Methanol in a 90:10 % v/v ratio, detected at 323 nm. Stress-testing study of STR was carried out through thermal, photolytic, hydrolytic, and oxidative conditions. The method’s greenness was estimated by using three tools including AGREEprep, ComplexGAPI, and analytical ecoscale where the method was found to be environmentally sustainable. Hydrolytic, oxidative, and thermal stability studies indicate moderate stability for STR, while the drug resists photolytic degradation. Two degradation products were identified by LC-MS with m/z 299.02 and 222.96. Linear calibration from 10 to 60 μg/ml, assay value 100.21 %w/w. The limit of detection and limit of quantification are 1.078 and 3.267 μg/ml. The optimized UPLC method was selective, precise, and accurate for the determination of STR in the presence of impurities and degradation products which will be useful for quality control in pharmaceutical industries.
Keywords: UPLC, LC-MS, impurity profiling, degradation pathways, strontium ranelate, stability testing